DEVELOPING POST COVID-19 POLICY RECOMMENDATION USING SCENARIO PLANNING FOR ROAD-BASED PUBLIC TRANSPORTATION COMPANY IN INDONESIA - Alfin, Timotius
COVID-19 pandemic in Indonesia brings huge impacts on the transportation sector, especially road-based public transportation. This impact is the reduction of demand for road-based public transportation. This trend was very dangerous for public transportation companies and becoming a concern of The Ministry of Transportation because public transportation is not only needed by the passenger but also has become a source of income for a lot of people including the driver, ticketing officer, terminal officer, and even cleaning service officer. Because of that, The Ministry of Transportation needs policy recommendations to solve these issues. To generate the policy recommendation, the author use scenario planning method that involves several stakeholders from the transportation industry as key informants. The scenario that has been developed consists of three plausible scenarios named Highway Scenario, Busway Scenario, and Gridlock Scenario. The Highway Scenario will happen if the COVID-19 pandemic in Indonesia can be handled in less than 1 year. This scenario represents the “Highway” condition where the road-based public transportation can accelerate its business and having recovery after the COVID-19 pandemic can be controlled Nationwide. The Busway Scenario will happen if the COVID-19 pandemic handling in Indonesia is prolonged more than 1 year, but the society starts to put high trust toward public transportation. This scenario represents the “Busway” condition where the road-based public transportation might need more efforts to maintain high public trust toward their service but eventually can gain revenue and keep sustainable by developing the new standards for the post-COVID-19 pandemic outbreak. The Gridlock Scenario will happen if the COVID-19 pandemic handling in Indonesia is prolonged more than 1 year, and society has low trust toward public transportation. This scenario represents the “Gridlock” condition where the road-based public transportation might be collapsing one by one due to diminishing demands and high fixed costs that cannot be covered by their operational activities. Each scenario will bring different implications & options to the road-based public transportation company. The emerging of each scenario also leads by different early warning signals that will be beneficial for The Ministry of Transportation in deciding which policies to implement in order to support road-based public transportation companies to be able to survive the post-COVID-19 pandemic situation.